Physical, Thermal, and Morphology Characteristics of Waste Latex Rubber Glove-Modified Bitumen - Auni Diyana Fadzil; Nur Izzi Md Yusoff; Shuhaida Harun; Khairiah Haji Badri; Iswandaru Widyatmoko; Faridah Hanim Khairuddin; Abdalrhman Milad; Munder Bilema; Naeem Aziz Memon (Advances in Civil Engineering)
Researchers across the globe have explored several alternatives to recycling natural rubber and have identified several challenges. Therefore, this study evaluates the feasibility of recycling waste latex rubber gloves (WLRG) as a bitumen modifier to enhance the bitumen’s physical, thermal, and morphological characteristics. The study adds varying percentages of WLRG (3%, 5%, 7%, and 9%) to the 60/70 bitumen and analyzes them to determine the optimum WLRG percentage. The penetration, softening point, ductility, and viscosity tests of the modified binders show a consistent pattern. All WLRG-modified bitumens are stable storage blends at high temperatures. The thermal characteristics of the WLRG particles in the modified bitumen are examined through thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The ogive graph shows that the weight loss of the bitumen modified with 3%, 5%, 7%, and 9% WLRG occurred at 457.5, 464.3, 462.2, and 459.5°C. The maximum weight loss of the control sample occurred at 465.6°C when the environment switched from nitrogen (N2) to air. The DSC graph reveals the changes in the structure or physiochemical processes of the WLRG. The melting point for the binders modified with 3%, 5%, 7%, and 9% WLRG is 133.6, 132.1, 103.5, and 133.2°C. The morphological characteristics were determined using atomic force microscopy (AFM). The bee structure gives a scientific explanation of the microstructural characteristics. A contact angle test was performed to identify the wettability of the sessile drop device by using three types of solvent, namely distilled water, formamide, and glycerol. The contact angle of water showed a decreasing trend, where the binder containing 9% WLRG had the lowest contact angle. For the control sample, the contact angles of formamide and glycerol are 73.95° and 71.85°, respectively. In summary, WLRG is a suitable bitumen modifier and can enhance the physical, thermal, and morphological characteristics of the asphalt binder.